2014
DOI: 10.1103/physrevlett.112.195702
|View full text |Cite
|
Sign up to set email alerts
|

Frozen Topology: Entanglements Control Nucleation and Crystallization in Polymers

Abstract: Polymer chains form lamellar structures during crystallization which display a memory of thermal history. Using molecular dynamics simulations and primitive path analysis, we show a direct dependence of both density and crystalline stem length on the local entanglement length. The slow relaxation of the entanglement state after a change of external conditions can directly explain the role of thermal history for polymer crystallization, in particular memory effects. The analysis of the local entanglement state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
156
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(170 citation statements)
references
References 25 publications
13
156
1
Order By: Relevance
“…The experimental evidence is consistent with a kinetic nature of melt memory . Even when cooling from the same melting temperature, the increase of crystallization temperature depends on molecular weight, the initial level of crystallinity or on how the standard crystalline state is prepared.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…The experimental evidence is consistent with a kinetic nature of melt memory . Even when cooling from the same melting temperature, the increase of crystallization temperature depends on molecular weight, the initial level of crystallinity or on how the standard crystalline state is prepared.…”
Section: Introductionsupporting
confidence: 73%
“…Other sources of self‐nucleation can be found in melts at temperatures a few degrees above the observed melting point. For example, it has been posited that self‐nuclei may derive from residual orientation of chain segments that formed the initial crystallites, from residual intermolecular interactions, from a heterogeneous distribution of crystalline sequences or from inhomogeneous entanglement redistribution …”
Section: Introductionmentioning
confidence: 99%
“…Hence, long ethylene sequences keep memory of the prior crystalline state reducing the entropy barrier for nucleation and facilitating a subsequent crystallization. Molecular dynamic simulations have also been carried out to demonstrate that slow relaxation of entanglements built during crystallization is the intrinsic cause of the melt memory effect …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11]15,16 However, there have been several investigations where any possible memory from such remnant crystalline domains is deliberately wiped out, but still observing melt-memory effects during second crystallization. 5,[12][13][14][17][18][19][20][21] As a classic example, Schultz observed that the maximum crystallization rate of linear polyethylene can be significantly lower if the sample was prepared at higher melt temperatures. 5 The same feature has been observed in other polymers as well.…”
Section: Introductionmentioning
confidence: 99%
“…As plausible explanation of this effect, existence of a precursor state, local clustering of chain segments in the molten state, and entanglement effects have been suggested in the literature. 13,17,19 Sometimes a distinction is made between two kinds of memory effects. 21 If the melt temperature is lower than the equilibrium melting temperature, some remnant crystalline domains could linger around and become responsible for melt-memory.…”
Section: Introductionmentioning
confidence: 99%